Behavior-Based Pricing, Production Efficiency, and Quality Differentiation - Jing, Bing (Management Science, 2017)
In a two-period vertical duopoly, we examine how behavior-based price discrimination (BPD) affects the firms’ endogenous quality differentiation and profits. The firms’ relative production efficiency, defined as the ratio between their unit cost difference and quality difference, plays a crucial role. With exogenous product qualities, BPD always decreases the profits of the more efficient firm, but increases those of the sufficiently less efficient firm. Anticipating its period 2 disadvantage in price discrimination, the less efficient firm competes more vigorously and also gains more in period 1 than its competitor. For the sufficiently less efficient firm, its period 1 gain dominates its period 2 loss, and its total profits increase. With endogenous quality choices, BPD does not alter the low-end quality (at the lower bound of the quality space), but increases the high-end quality, enlarging quality differentiation. This is because under BPD, each firm’s profit gain decreases (or its profit loss increases) in its relative production efficiency. Interestingly, BPD may increase both firms’ profits under endogenous quality differentiation. Aside from causing mismatch between consumers and products, we further show that BPD lowers social welfare through inducing excessive quality differentiation. This paper was accepted by J. Miguel Villas-Boas, marketing.